Early contribution of morphological awareness to literacy skills across languages varying in orthographic consistency - Desrochers, Alain; Manolitsis, George; Gaudreau, Patrick; Georgiou, George (Reading & writing, 2018)
In the present study, we examined the role of morphological awareness in reading and spelling performance across three languages varying in orthographic consistency (English, French, and Greek), after controlling for the effects of phonological awareness and rapid automatized naming (RAN). One hundred fifty-nine English-speaking Canadian, 238 French-speaking Canadian, and 224 Greek children were assessed at the beginning of Grade 2 on measures of morphological awareness, phonological awareness, and RAN. At the end of Grade 2, they were assessed on reading accuracy, reading fluency, reading comprehension, and spelling to dictation. The results indicated that morphological awareness was a unique predictor of reading comprehension and spelling in all three languages, of reading fluency in English and French, and of reading accuracy in English only. Furthermore, the results of multigroup analyses revealed no significant differences in the contribution of morphological awareness to the literacy outcomes across languages. Theoretical and practical implications of these finding are discussed.